Narratives on the Inclusion of Autistic Students: Challenges and Teaching Practices - Luz, Mariana Helena Silva Da (2017)
Autism is a widely explored theme in the literature. Nevertheless, school inclusionamong autistic children still constitutes a challenge. On this basis, the generalgoal of this research was to identify the challenges of teaching practices in themonitoring of an autistic student and in which conditions his inclusion occurs.The qualitative research, descriptive and exploratory in its nature, is characterizedas a case study that was conducted in the months of August to October 2014 in aprivate institution of Brasilia. In summary, the study, by means of semi-structuredinterviews and on-site observations, concluded that the school»s inclusionproposal, in which parents seem to trust, is weakened by the lack of professionalpreparation, a fact derived by the precariousness of initial and continuous trainingof these professionals.